The results of a randomized trial looking at 24 weeks vs 48 weeks of treatment with peginterferon alpha-2a (40 kDa) and ribavirin combination therapy in patients with chronic hepatitis C genotype 1 - Brandao, C.; Barone, A.; Carrilho, F.; Silva, A.; Patelli, M.; Caramori, Carlos Antonio [UNESP]; Focaccia, R.; Pereira, L.; Pedroso, M.; Tatsch, F.; Pessoa, M. (Blackwell Publishing, 2006)
Peginterferon-alpha plus ribavirin is the most effective therapy for chronic hepatitis C. This study was designed to evaluate the effect of peginterferon alpha-2a (40 kDa) plus ribavirin on sustained virological response (SVR) when administered for 24 vs 48 weeks in genotype 1 naive patients. One hundred and seventeen patients were enrolled in this controlled trial. Genotype 1 patients were randomized to 24 weeks treatment vs 48 weeks treatment. Genotype non-1 patients received 24 weeks treatment as an observational group. Outcomes were SVR (defined by hepatitis C virus-RNA-negative at week 24 of follow-up) and tolerability across the study period. The end-of-treatment response was 59% for genotype 1 (24 weeks treatment), 80% for genotype 1 (48 weeks treatment) and 92% for genotype non-1 (24 weeks treatment). The end-of-follow-up response was 19% (95% confidence interval (CI): 7.2-36.4) (genotype 1, 24 weeks) and 48% (95% CI: 30.2-66.9; P = 0.0175) (genotype 1, 48 weeks). Among genotype non-1, SVR was 76% (95% CI: 62.3-86.5). There were no unexpected adverse events.Almost half of the genotype 1 patients achieved an SVR after 48 weeks treatment with peginterferon alpha-2a (40 kDa) and low-dose ribavirin and confirmed that they should be treated for 48 weeks. Safety profile was acceptable.
Keywords: hepatitis C; peginterferon alpha-2a; ribavirin; treatment duration